Oxidized phospholipids are biomarkers, drug targets, and drug leads - Oskolkova, Olga V.; Birukova, Anna A.; Birukov, Konstantin G.; Bochkov, Valery N. (Frontiers in Drug Discovery, 2022)
Enzymatic oxidation or autooxidation of esterified polyunsaturated fatty acids (PUFA) residues within phopsholipids forming cell membrane or contained in circulating lipoprotein particles leads to formation of a broad range of oxidized phospholipid (OxPL) species. Chronically elevated OxPL levels present in circulation and atherosclerotic plaques are thought to induce proinflammatory and injurious effects on endothelial cells (EC) and other cell types. On the other hand, acute elevation of circulating OxPLs has been also observed in ARDS and sepsis patients. Increased baseline levels of OxPL in aging models associated with age-dependent decline of antioxidant defense were responsible for exacerbated inflammation and lung jnury caused by bacteria-derived factors. However, analysis of the structure–activity relationship also identified specific OxPL products exhibiting prominent anti-inflammatory, pro-survival and barrier protective properties. This minireview will briefly discuss biological properties of OxPLs that are increasingly recognized as biomarkers of oxidative stress, but also potential drug targets and drug leads.